Analisis Rantai Pasok Tempe Di Desa Loh Sumber Kecamatan Loa Kulu - Trisnawati, Sarifah Huri; Drianti, Astik; Rahmawati, Eka (Rawa Sains: Jurnal Sains STIPER Amuntai, 2025)
Tempe is a traditional food made from soybeans and other ingredients. The fermentationof tempe uses a type of mold called Rhizopus. Rhizopus is a mold that can produce various enzymes.Soybeans are high in protein and also rich in other nutrients. In terms of cost, soybeans are the mostaffordable protein source, allowing most of the plant protein needs to be met through soybeanprocessing. Soybeans should not be consumed raw because they contain trypsin inhibitors. Cookingsoybeans neutralizes the trypsin inhibitors. The objective of this study is to examine the supply chain of tempe daun (leaf tempe) in Loh Sumber Village, Loa Kulu District. This includes determining the marketing costs, marketing margins, and share margin for each channel, as well as assessing themarketing efficiency of tempe daun in Loh Sumber Village, Loa Kulu District. Data collection was carried out through direct interviews with respondents using questionnaires and direct fieldobservations. The results of this study show that there are 2 marketing channels in the supply chainof tempe daun in Loh Sumber Village, Loa Kulu District. The production cost of tempe daun in Loh Sumber Village, Loa Kulu District for channel 0 is IDR 338.06 per pack, and the marketing cost for channel 1 is IDR 29.82. Since there is only a producer-to-trader channel, the highest margin is in channel 1, which is IDR 132.02 per pack, and the highest share margin is also in channel 1 at 0.77%. For channel 1, the efficiency calculation indicates positive results. Keywords: Supply Chain, Tempe Daun, Marketing Costs, Margin, Efficiency